Punching shear strength of edge column connections of rectangular flat plates - Zamani Zavieh, Shahram (University of Ottawa (Canada), 2003)
Edge column slab connections of continuous flat plate structures, under combined shear and moment transfer, can be susceptible to failure by punching shear. A 2 bay by 2 bay, rectangular flat plate, panel aspect ratio 2:1, was fabricated and loaded to failure under a simulated uniformly distributed load. The edge and corner columns were supported so that the reactions and reactive moments could be measured. The interior column, no moment transfer, punching shear strength was less than inferred from previous research. Based upon the strain gauge results neither the long or short direction flexural reinforcements yielded. The fact that the interior column was rectangular in section was a complication. Comparison of the measured reactions to those calculated by finite element analysis, FEM, and a modified direct design method, RDDM shows that both methods predict the reactions with acceptable accuracy. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.; Engineering, Mechanical.